An Analysis of Social Anxiety of the Students’ EFL Writing Skill - Nurdianingsih, Fitri; Taufiqur Rohmah, Ima Isnaini; Jayyidah, Nazzah Yusva (CV. Zabags Qu Publish, 2023)
the aim of this research is about an analysis of social anxiety of the students in writing skill. The participant of this research were 45 students of English Education Study Program at IKIP PGRI Bojonegoro. A qualitative research design was used in this research. The questionnaire was given to collect the data related to the types of students’ anxiety of the participants. The result showed that the mean of writing anxiety range from 17,3 to 22. The average score for avoidance behavior is 17,3, somatic anxiety is 20, and cognitive anxiety is on average 22. This study educates teachers about three aspects of student writing anxiety, including its forms as well as the variables that contribute to it. In order to help students reduce or eliminate their writing anxiety, this study also suggests that teachers act as the students' prompter and tutor in the classroom. By doing this, the students' writing skills will improve.